Analysis of the volleyball spike. Relationships between several parameters and the speed of the ball - Cloes, M.; Croisier, J. -L.; Barsin, M.; Ciccarone, G.; Forthomme, B. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Difference in hitting height could be explained by higher jump performance (both groups had the same results on arm reach) but also by better spike timing. Being higher, top level athletes would have more opportunities to hit the ball, especially as they develop better throwing qualities. The latter can be related to better muscular performances of the internal rotator muscles as pointed out by isokinetic testing